2005
DOI: 10.1016/j.ydbio.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 inhibits branching morphogenesis in the prostate gland and interferes with Notch signaling

Abstract: The mouse prostate gland develops by branching morphogenesis from the urogenital epithelium and mesenchyme. Androgens and developmental factors, including FGF10 and SHH, promote prostate growth (Berman, D.M., Desai, N., Wang, X., Karhadkar, S.S., Reynon, M., Abate-Shen, C., Beachy, P.A., Shen, M.M., 2004. Roles for Hedgehog signaling in androgen production and prostate ductal morphogenesis. Dev. Biol. 267, 387-398; Donjacour, A.A., Thomson, A.A., Cunha, G.R., 2003. FGF-10 plays an essential role in the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 61 publications
8
139
0
Order By: Relevance
“…The observed increased potency of BMP2/7 (compared with BMP2 or BMP7 alone) may, therefore, at least in part be caused by the increase in bioavailability due to the diminished efficacy of locally produced Noggin. Of note, BMP7 inhibits epithelial proliferation, branching morphogenesis and ductal budding in the normal development of the prostate, and is also associated with decreased Notch signaling (Grishina et al, 2005), a critical pathway during morphogenesis of epithelial tissues. In this context, the BMP antagonist Noggin can have a key regulatory role in BMP4 and BMP7 action in tissue epithelial stem cells (Cook et al, 2007).…”
Section: Bmp2/7 Inhibits the Breast Cancer Stem Cell Subpopulation Jtmentioning
confidence: 99%
“…The observed increased potency of BMP2/7 (compared with BMP2 or BMP7 alone) may, therefore, at least in part be caused by the increase in bioavailability due to the diminished efficacy of locally produced Noggin. Of note, BMP7 inhibits epithelial proliferation, branching morphogenesis and ductal budding in the normal development of the prostate, and is also associated with decreased Notch signaling (Grishina et al, 2005), a critical pathway during morphogenesis of epithelial tissues. In this context, the BMP antagonist Noggin can have a key regulatory role in BMP4 and BMP7 action in tissue epithelial stem cells (Cook et al, 2007).…”
Section: Bmp2/7 Inhibits the Breast Cancer Stem Cell Subpopulation Jtmentioning
confidence: 99%
“…Epidermal growth factor (Saito and Mizuno, 1997), homeobox genes (Podlasek et al, 1997;Warot et al, 1997), and both low-dose and high-dose estrogens (vom Saal et al, 1997) have been shown to influence budding, but the mechanisms by which these effects occur is unclear. The bone morphogenetic proteins (BMPs) 4 and 7 (Cook et al, 2007;Grishina et al, 2005) and wingless integration site A (WNT5A; unpublished observations) can directly inhibit bud formation while hedgehog (Hh) signaling has been implicated as a positive regulator of budding (Podlasek et al, 1999;Lamm et al, 2002;Doles et al, 2006). What remains to be determined is how these positive and negative influences are orchestrated to yield the reproducible pattern and quantity of buds that form on select surfaces of the male mouse UGS during fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…There are no significant changes in the expression of Shh, FGF7, FGF10 or BMP7, known to inhibit branching morphogenesis in the prostate. 42 In the pes-ERaKO, expression levels of these genes showed no significant difference. We also observed that expression of IGF-1 decreases and BMP4 increases in the DLP of FSP-ERaKO (Figure 6b).…”
Section: Prostate Branching Morphogenesis In Fsp-mentioning
confidence: 94%